The Concept of "Female Beauty" In Tatar and Yakut Literature - Gabdulbarovna Mukhametzyanova, Flera (2020)
In this research is focused on studying the features of representation of the concept of "female beauty" in the literature of Turkic peoples illustrated by writing of the founders of Tatar and Yakut literatures. The subject of the research is the means of representation of this concept in the works of GM Tukay "Tatar kyzlaryna" ("To Tatar girls", 1906) and AE Kulakovsky "Kyrasyabay Kyys" ("Beautiful girl", 1910). Common and distinctive features in representation of female personages in the works of the two poets were revealed in the course of comparative analysis. The relevance of the research is due to good perspectives of studying the concept a basis, revealing the worldview of people. At the same time,